How to finance the transition to low-carbon energy in Europe?. (December 2020) - Polzin, Friedemann; Sanders, Mark
Abstract: In this paper, we use standard scenarios focussing on renewable energy, energy efficiency and grid investments. We take stock of the literature and quantitative data on available sources of financing for clean energy to qualitatively match supply and demand of specific sources of finance in the European context. Our analysis shows that under the current investment mandates and lending criteria the required funds for a successful energy transition are available. In fact, the current landscape of financing sources can provide between two and six times what is necessary. However, institutional investors and lenders such as pension funds and banks in particular are reluctant to invest in the renewable energy or grid infrastructure because of expected (policy) discontinuities. In addition, more venture capital and household investment are needed to finance low-risk small-ticket projects in the early stages of innovative clean energy technologies, to complement the abundantly available funds for large-scale investments. Based on our analysis, we develop a matrix indicating the role and availability of different sources of finance and new intermediation channels in the energy transition and how these should be deployed. Highlights: This study contrasts the demand for and (potential) supply of financial resources for the European energy transition. It identifies a qualitative mismatch between the available sources and the required investments up to 2050. The involvement of institutional investors and risk-carrying capital is particularly limited. A matrix indicating role and availability of different sources provides a guide to the involvement of financiers. Tailor-made policies and practical implications are developed for each source of funding.